PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITE PADA TEMA 1 INDAHNYA KEBERSAMAAN SUBTEMA 1 KEBERAGAMAN BUDAYA BANGSAKU PEMBELAJARAN 1 DI KELAS IV SD NEGERI 101771 TEMBUNG - Zulaiha, Siti; Rozi, Fahrur; Mailani, Elvi; Simanjuntak, Eva Betty; Simanjuntak, Sorta (Universitas Negeri Medan, 2024)
This research aims to produce Google site products and to determine the validity, practicality and effectiveness of the Google site. This research was carried out in class IV of the 101771 Tembung State Elementary School. This research is Research & Development (R&D) research using the ADDIE model, namely (Analysis), Design, Development, Implementation and Evaluation. Google site product development validation is developed based on material expert assessments. and media experts. Based on the results of material expert validation in stage 1, media expert validation results before revision had an average of 88% in the Very Appropriate category. After revision, material expert validation results had an average of 98% in the very appropriate category. Results media expert validation before revision, obtained a percentage of 56% in the Fairly Appropriate category. After revision, the media expert validation results obtained a percentage of 90% in the Very Appropriate category. The results of the practicality of Google site development were implemented through small group trials and large group trials. Response students in small group trials, obtained an average of 92% in the very applicable category. Teacher responses in small group trials obtained an average of 80% in the very applicable category. Student responses in large group trials obtained an average of 97% in the very applicable category. Teacher responses in large group trials obtained an average of 97% in the very applicable category. Product effectiveness results are based on calculating the results of students' pretest and posttest scores. The students' pretest scores obtained a classical average score of 69 with incomplete criteria. Meanwhile, students' posttest scores obtained a classical average score of 93 with complete criteria. So it can be concluded that the use of Google site as a learning medium in class IV of the 101771 Tembung State Elementary School is very effective. Keywords: Google site learning media development, learning outcomes